Development and adaptation of the technology of air biotreatment in trickle-bed bioreactor to the automotive painting industry. (1st August 2021) - Kasperczyk, Damian; Urbaniec, Krzysztof; Barbusiński, Krzysztof; Rene, Eldon R.; Colmenares-Quintero, Ramon F.
Abstract: The automotive painting industry is a source of environmental pollution caused by Volatile Organic Compounds (VOCs) present in the discharged ventilation air. To contribute to the mitigation of this type of air pollution, Ekoinwentyka Ltd. developed – from pilot scale to full scale – and adapted the technology of Compact Trickle Bed Bioreactor (CTBB) whose operating principle builds upon co-current downflow of the gas phase (polluted air) and liquid phase (solution of mineral salts) through a packed bed where active microorganisms are immobilized in the biofilm on the surfaces of packing elements. Pilot-scale bioreactor 0.32 m in diameter and 1.50 m total height had its packed bed inoculated with a consortium of microorganisms dominated by Pseudomonas fluorescens bacteria. During the experimental programme that lasted several months, the flow rate of air drawn from the ventilation system of the painting shop was changing between 1.0 and 10.0 m 3 /h and the inlet concentration of VOCs ranged from 10 to 200 ppm. By measuring VOC concentration in the purified air, the factor of VOC biodegradation was found to range between 85 and 99%. Based on pilot-scale experiments, full-scale CTBB has been developed 2.8 m in diameter and 10 m total height and installed as an add-on component of the ventilation system of the painting shop. Test operation at gas flow rates up to 6000 m 3 /h, confirmed VOC biodegradation factor at the level of 85–99% thus proving a positive result of CTBB technology adaptation to the conditions of the automotive painting industry.